8. TALES FROM BEYOND THE WALL: BLOOD-BRAIN BARRIER AND BLOOD-GUT BARRIER DYSFUNCTION IN PSYCHOSIS. (9th April 2019) - Pollak, Thomas
Abstract: Blood-brain barrier pathology is recognized as a central factor in the development of many neurological disorders, but much less is known about the role of the blood-brain barrier in psychiatric disorders. Similarly, blood-gut barrier dysfunction is increasingly recognized as an important contributing factor in medicine far beyond narrowly-defined gastroenterological disorder, with neuropsychiatric disorders such as schizophrenia the focus of recent attention. Furthermore, in schizophrenia research there has been heightened interest in the aetiological role of systemic inflammation/immune responses and diet. As the blood-brain and blood-gut barriers are the chief interfaces via which systemic factors can influence the brain, they are a natural focus of interest to understand the neurobiology of psychotic disorders, potentially also representing a novel constellation of therapeutic targets. Measurement of blood-brain and blood-gut barrier function in humans is far from straightforward, a state of affairs which has perhaps led to barrier function research in psychosis being sidelined in the past. However new methodologies and models have enabled a new wave of research, bolstered by fundamental advances in our understanding of concepts such as neuroimmune privilege, the gut-brain axis, the role of the microbiome and brain autoimmunity. In this symposium, we will take a multidisciplinary tour of recent exciting developments focusing on multiple aspects of barrier dysfunction in the pathogenesis of psychotic disorders. Experts from the field of clinical psychiatry, neuroimmunology, genetics and epidemiology will be invited to share their findings and thoughts on the future of barrier function research in psychosis. We will explore the following questions: - Is there evidence for blood-brain and blood-gut barrier dysfunction in psychotic disorders? - Does barrier function cause psychotic disorder or is it a consequence of another pathology? - Is there a role for measurement of barrier function in the clinical management of patients with psychosis? - How does blood-gut barrier dysfunction impact the blood-brain barrier? - What is the significance of barrier function in light of recent immunological and inflammatory hypotheses of psychotic disorders, including neuronal autoantibody-associated psychosis? - Do schizophrenia-relevant genetic polymorphisms affect barrier function? - Could diet affect barrier function in a way that is relevant to the development of psychotic disorders? - How does the microbiome or systemic infection affect barrier function in psychotic disorders? - Could restitution of impaired barrier function represent a fruitful therapeutic strategy for the treatment of psychotic disorders? Dr. Bob Yolken will be the discussant, drawing on an extensive experience of schizophrenia research at the intersection of microbiology, immunology, genetics and epidemiology.